2012
DOI: 10.1142/s0217984912500881
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR DYNAMICS STUDY OF THE DISRUPTION OF H-BONDS BY WATER MOLECULES AND ITS DIFFUSION BEHAVIOR IN AMORPHOUS CELLULOSE

Abstract: Hydrolysis is an important component of the aging of cellulose, and it severely affects the insulating performance of cellulosic materials. The diffusion behavior of water molecules in amorphous cellulose and their destructive effect on the hydrogen bonding structure of cellulose were investigated by molecular dynamics. The change in the hydrogen bonding structure indicates that water molecules have a considerable effect on the hydrogen bonding structure within cellulose: both intermolecular and intramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Structurally, it is estimated that there is a thin layer of non-crystalline cellulose on the surfaces of fibrils (Atalla et al 2008;Fernandes et al 2011;Leppänen et al 2009;Salmén and Bergström 2009;Weatherwax 1977) that could be prone to hornification and interfibrillar hydrogen bonding to either cellulose or hemicellulose (Leppänen et al 2009;Mohan et al 2012). Modeling studies on a molecular level have also suggested that intrafibrillar restructuring can take place within the first molecular layers (Heiner et al 1998;Matthews et al 2006;Maurer et al 2013), however, the nature and extent of such restructuring depend on the amorphous fraction and crystal structure of the surface (Kulasinski et al 2017;Liao et al 2012;Yamane et al 2006). Figure 1 shows the possible changes including surface irregularities and hydrogen bond changes (red lines) from inter-chain (bulk cellulose, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it is estimated that there is a thin layer of non-crystalline cellulose on the surfaces of fibrils (Atalla et al 2008;Fernandes et al 2011;Leppänen et al 2009;Salmén and Bergström 2009;Weatherwax 1977) that could be prone to hornification and interfibrillar hydrogen bonding to either cellulose or hemicellulose (Leppänen et al 2009;Mohan et al 2012). Modeling studies on a molecular level have also suggested that intrafibrillar restructuring can take place within the first molecular layers (Heiner et al 1998;Matthews et al 2006;Maurer et al 2013), however, the nature and extent of such restructuring depend on the amorphous fraction and crystal structure of the surface (Kulasinski et al 2017;Liao et al 2012;Yamane et al 2006). Figure 1 shows the possible changes including surface irregularities and hydrogen bond changes (red lines) from inter-chain (bulk cellulose, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While constraints from the combination of large-scale structure, CMB data and SNIa observations could reduce the allowed space-parameter to a small region around the ΛCDM cosmology (β ≈ 10 −3 ) [13,42], other analyses combining CMB and BAO data yield (n, β) = (0.027 +0.42 −0.23 , 4.63 +2.73 −10.6 ) [8]. These values were later improved with combinations of CMB, SNIa and BAO data, along with Hubble parameter estimations [55][56][57], as well as data coming from strong lensing analysis [14,58]. Cosmographic constraints were obtained from the examination of the deceleration parameter [48] and the so-called statefinder diagnostic [46].…”
Section: Power Law Gravity: F (R) = R − β/R Nmentioning
confidence: 99%
“…A cosmographic approach. The geometric and kinematic properties of the metric (14) are characterised by the so-called kinematic parameters, defined as the coefficients of the series expansion of the scale factor around t 0 . In particular,…”
Section: The Redshift Driftmentioning
confidence: 99%
See 1 more Smart Citation
“…42 −0.23 , 4.63 +2.73 −10.6 ) [58]. These estimates were further upgraded with amalgamations of BAO, SNIa, CMB data, coupled with Hubble parameter evaluations [71,72], and strong lensing analysis [73,74]. From the investigation of deceleration parameter and statefinder diagnostics, cosmographic constraints were reported in [59,61].…”
Section: F (R) Gravity Modelsmentioning
confidence: 99%